Aldoxorubicin-loaded nanofibers are cytotoxic for canine mammary carcinoma and osteosarcoma cell lines in vitro: A short communication. (February 2020) - Stokol, Tracy; Wan, Chris; Blakely, Robert; Bellat, Vanessa; Law, Benedict
Abstract: Chemotherapeutic drugs are given parenterally to treat various canine tumors. A limitation of parenteral administration is low drug penetration into the tumor, which reduces tumoricidal activity. Various drug carriers have been used to enhance tumor delivery, including albumin, liposomes and nanoparticles. A novel peptide-based nanofiber precursor (NFP) has been developed that is designed to take advantage of the leaky tumor neovasculature to promote drug delivery after parenteral administration. In this study, we loaded aldoxorubicin, an albumin-bound prodrug version of doxorubicin, onto NFP and tested the in vitro cytotoxicity in canine mammary carcinoma (CMT12, CMT25) and osteosarcoma (HMPOS, D-17, Abrams) cell lines. The half maximal inhibitory concentration (IC50) was determined with a luminescence-based cell viability assay. The IC50 for aldoxorubicin-loaded NFP was lower than free aldoxorubicin or doxorubicin in all cell lines, whereas non-drug loaded NFP had no cytotoxic effects. There were differences in IC50 between the osteosarcoma lines, with lower and higher IC50 for HMPOS and D-17 cells, respectively, with all drugs (aldoxorubicin-loaded NFP, free aldoxorubicin or free doxorubicin). Our results indicate that drug-loaded NFPs are cytotoxic for various canine mammary carcinoma and osteosarcoma cell lines in vitro and hold promise as a mechanism for enhancing delivery of chemotherapeutic agents to canine tumors. Highlights: We tested aldoxorubicin-laced nanofiber peptide (Aldox-NFP) cytotoxicity in canine mammary carcinoma and osteosarcoma cells Aldox-NFP had a lower half maximal inhibitory concentration versus free drug (aldoxorubicin or doxorubicin) Tumor cells showed variable drug sensitivity, with HMPOS and D-17 having the highest and lowest sensitivity, respectively Drug-loaded NFP is a potential new way to deliver chemotherapeutic agents to canine mammary and bone tumors